2012
DOI: 10.1007/s12031-012-9842-1
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A Enhances Glutamate Transporter GLT-1 mRNA Levels in C6 Glioma Cells via Neurosteroid-Mediated Cell Differentiation

Abstract: The neurotoxic effects of excitatory amino acids (EAAs) are suggested to be connected with the chronic loss of neuronal cells, thereby being responsible for the age-related neurodegenerative diseases. Therefore, it seems conceivable that the excitatory amino acid transporters may contribute to the protection of neuronal cells against the excitotoxic damage by facilitating the removal of EAAs from the brain tissue. On the other hand, previous studies have suggested that glial cell differentiation may be involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…YY1 recruits epigenetic corepressors to exert its repressive gene regulation (18). Given the role of HDAC inhibitors in upregulation of glutamate transporter gene expression (27), we determined if HDACs play a corepressor role in YY1-induced EAAT2 inhibition. First, we studied the effect of overexpression of HDAC subtype members belonging to classes I and II on EAAT2 promoter activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…YY1 recruits epigenetic corepressors to exert its repressive gene regulation (18). Given the role of HDAC inhibitors in upregulation of glutamate transporter gene expression (27), we determined if HDACs play a corepressor role in YY1-induced EAAT2 inhibition. First, we studied the effect of overexpression of HDAC subtype members belonging to classes I and II on EAAT2 promoter activity.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the neuroprotective effects of HDAC inhibitors in various neurodegenerative disease models (see reference 28 for a review). Moreover, HDAC inhibitors afford neuroprotection by upregulating glutamate transporters (27). Accordingly, we addressed the role of HDACs in EAAT2 regulation and Mn repression of EAAT2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone acetylation modification is characterized by the addition and removal of acetyl moiety from acetyl-coenzyme A to the ε-amino group of lysine residue; this reaction is carried out by two enzymes, histone acetyltransferases (HATs) and histone deacetylases (HDACs) [71]. Histone deacetylases (HDACs) inhibitors, such as TSA and valproic acid (VPA) increase EAAT2 mRNA and protein levels, indicating the role of acetylation in regulating EAAT2 expression [64, 72, 73]. In addition, CREB-binding protein (CBP), a HAT, has been reported to contribute as a co-repressor of YY1 in the negative regulation of EAAT2 [26].…”
Section: Epigenetic Deregulation In Neurological Disordersmentioning
confidence: 99%
“…Mn-induced oxidative stress may also repress GLT-1 promoter activity because oxidative stress has been reported to be a causal factor for impairment of GLT-1 in experimental and clinical studies. [122][123][124][125] YY1 also interacts with an epigenetic modifier HDAC1, which is enhanced by Mn, 65 indicating that HDACs serve as co-repressors of YY1 and inhibition of HDACs with pharmacological inhibitors increases GLT-1 promoter activity 126,127 and attenuates Mn-reduced GLT-1 promoter activity. 65 …”
Section: Yy1 Is a Negative Regulator Of The Glt-1 Promotermentioning
confidence: 99%